2021
DOI: 10.1038/s41598-021-95756-3
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral image processing for the identification and quantification of lentiviral particles in fluid samples

Abstract: Optical spectroscopic techniques have been commonly used to detect the presence of biofilm-forming pathogens (bacteria and fungi) in the agro-food industry. Recently, near-infrared (NIR) spectroscopy revealed that it is also possible to detect the presence of viruses in animal and vegetal tissues. Here we report a platform based on visible and NIR (VNIR) hyperspectral imaging for non-contact, reagent free detection and quantification of laboratory-engineered viral particles in fluid samples (liquid droplets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The lower classification accuracies obtained when applying the calibration models built from macroscopic VNIR or combined VNIR-SWIR data to the second test set indicate potential model overfitting (especially for the SVM model) and a lack of discrimination ability based on the mean spectra. These results can be compared to a recent study in which it was shown that VNIR spectral imaging could be used to identify and quantify the presence of lentiviral particles in dried fluid samples 15 and to previous work on VNIR microscopic imaging for the classification of live bacterial cells 31 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The lower classification accuracies obtained when applying the calibration models built from macroscopic VNIR or combined VNIR-SWIR data to the second test set indicate potential model overfitting (especially for the SVM model) and a lack of discrimination ability based on the mean spectra. These results can be compared to a recent study in which it was shown that VNIR spectral imaging could be used to identify and quantify the presence of lentiviral particles in dried fluid samples 15 and to previous work on VNIR microscopic imaging for the classification of live bacterial cells 31 .…”
Section: Resultsmentioning
confidence: 92%
“…Of particular note is a study on the use of VNIR macroscopic imaging for the classification of colonies of pathogenic bacteria related to urinary tract infections, cultured on blood agar 14 , in which a variety of chemometric approaches were evaluated to classify colonies at the colony level. More recently, spectral imaging has been developed for the identification and quantification of lentiviral particles in fluid samples 15 and for primary screening at the point-of-care of SARS-CoV-2 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Geng et al [61] state that the agri-food industry has a large amount of waste generation industry and requires a comprehensive strategy for recycled and reused waste [62]. The products and materials from the agri-food industry can be recycled and can be reused [63], but internal and external stakeholder participation is required for waste collection and adoption of CE principles. This could result in social and economic advantages in developed or developing nations and create an opportunity to reduce environmental effects [64][65][66][67].…”
Section: Ce Principles Encircle Economic and Environmental Performancementioning
confidence: 99%
“…They range from the detection of the Zika virus in mosquitoes fed with infected human blood using infra-red spectroscopy [29] to the detection of hepatitis B and C viruses [30] and Dengue [31] in human samples using Raman and fluorescence spectroscopy. Most recent efforts aim to detect SARS-CoV-2 models [32] and the SARS-CoV-2 virus [33] , [34] , [35] , [36] .…”
Section: Introductionmentioning
confidence: 99%